Teaching foreign language in higher education: development of a new concept and modeling new communication technologies (Journal of Educational Sciences, 2018)
The article deals with applied problems of teaching foreign languages in non-linguistic environmentand for non-linguistic specialties in the perspective of new learning paradigms using modern teachingtechnologies. The results of the research show the need to develop a new modern concept of teachinga foreign language as a language for professional communication. The methodological basis of suchconcept can serve as the key for methods of teaching aimed at teaching strategies in non-linguistic environment.The paradigm of learning a foreign language undergoes several stages of its development,depending on the target task that this or that time puts forward. Current approaches of teaching foreignlanguages with all its uniqueness and effectiveness was used in Soviet period and the labor market of thattime, now it requires a cardinal revision due to the fact that not only the target task of studying foreignlanguages has changed, but the market demand as well. At present, higher tasks are imposed on a foreignlanguage, which are dictated by the labor market, where the goal of learning is to master a foreignlanguage not only for extracting information from foreign sources and reading literature, but mostly forprofessional communication. The era of globalization, integration of systems, business processes, all thisrequires mastering a foreign language at a professional level.